Dynamic evaluation of vertebral alveolar echinococcosis using MR T2 mapping - Jinhuan Han; Yushan Chang; Hui Guo (Journal of Orthopaedic Surgery)
Objective To explore the diagnostic value of MR T2 mapping in monitoring and evaluating the rabbit vertebral model with Echinococcus multilocularis infection. Materials and methods 24 New Zealand white rabbits were randomly divided into the experimental group ( n = 16), saline control group ( n = 4), and blank control group ( n = 4). The experimental group underwent surgery to drill holes on the surface of the spinous process of the 12th thoracic vertebra, fill it with a gelatin sponge, and adsorb multilocular hydatid suspension. The saline control group received an operation with saline, and the blank control group did not receive any intervention. The model rabbits were dynamically evaluated by routine MRI and MR T2 mapping once a month after surgery, 6 times. Two rabbits with positive imaging results were randomly selected every 2 months for histopathological examination to evaluate the severity and pathological features of the rabbit model with Echinococcus multilocular infection. Results There was no significant difference in the T2 mapping values between the diseased vertebrae and the undiseased vertebrae in the experimental group at the 1st month after surgery ( t = 1.7, p = .119), and the differences were statistically significant at the 2nd to 6th month after surgery ( p < .05). In the 1st and 2nd months after an operation, there was no significant difference in T2 values between the vertebrae of the saline control group, the blank control group, and the experimental group. In the third, fourth, fifth, and sixth months after surgery, the vertebrae of the experimental group were compared with that of the saline control group and the blank control group, and the difference was statistically significant ( p < .05). There was no significant difference in T2 mapping values every month after surgery between the saline control group and the blank control group ( p > .05). Conclusion The MR T2 mapping technique can quantitatively evaluate the changes of vertebral alveolar echinococcosis, and it shows sensitivity to pathological changes in vertebrae prior to detectable damage using conventional MRI; this offers potential for early detection of vertebral alveolar echinococcosis.